Effectiveness of Rehearsal Mechanism on CAD Learning Performance with Using Interactive Multimedia - Allafi A-Rahman, Mosa (International Journal of Engineering Research, 2023)
This study was seeks to examine the effects of the rehearsal mechanism on the new CAD learner’s practice performance (PP). An attempt was made to establish if rehearsing the CAD information increased the learners’ retention and improved their practice performance over those who did not rehearse. 29 new CAD learners were the participants in this study and were randomly divided into approximately two equal groups. Group one had rehearsed the CAD information over time (three times during one week only), while the other group did not rehearse the CAD information at all. Both groups were asked to created identical CAD tasks by following the same CAD multimedia presentation of an interactive media of ‘audio and animation’ modes. The results indicated that the rehearsal mechanism shortened the learning time and enhanced drawing accuracy, in contrast to the non-rehearsal option.